1993
DOI: 10.1038/bjc.1993.200
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of a cohort of French uranium miners exposed to relatively low radon concentrations

Abstract: Summary A cohort mortality study has been performed on French uranium miners having experienced more than 2 years of underground mining, with first radon exposure between 1946 and 1972

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 12 publications
5
48
0
1
Order By: Relevance
“…Previous analyses of the same cohort over a shorter follow-up period yielded an SMR for diseases of the circulatory system that was 0.88 of that of the general Newfoundland population (12). This value is consistent with that of other studies of miners exposed to radon progeny (9,(15)(16)). An elevated SMR was found for a cohort of sulfide ore miners exposed to radon progeny (17).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous analyses of the same cohort over a shorter follow-up period yielded an SMR for diseases of the circulatory system that was 0.88 of that of the general Newfoundland population (12). This value is consistent with that of other studies of miners exposed to radon progeny (9,(15)(16)). An elevated SMR was found for a cohort of sulfide ore miners exposed to radon progeny (17).…”
Section: Discussionsupporting
confidence: 80%
“…Some of these studies have reported a decreased standardized mortality ratio (SMR) for CHD among miners when compared with that of the general population (9,(15)(16). Conversely, an elevated SMR for CHD was found for a for several causes of death and may therefore mask real effects (18).…”
mentioning
confidence: 99%
“…These results confirmed those of previous analyses of this cohort (26). Similarly, other studies of radon-exposed miners have found no excess risk of CSD mortality (17,33,40).…”
Section: Mortality From Circulatory System Diseasessupporting
confidence: 82%
“…Previous publications have described the development of a French cohort of uranium miners (26,34,35). The cohort comprised 5086 individuals.…”
Section: Cohort Description and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation